2001
DOI: 10.1016/s0016-7037(00)00562-7
|View full text |Cite
|
Sign up to set email alerts
|

Archaeal lipids in Mediterranean cold seeps: molecular proxies for anaerobic methane oxidation

Abstract: Abstract-We investigated the distributions and ␦ 13 C values of biomarkers for Archaea associated with anaerobic methane oxidation in disparate settings throughout two Eastern Mediterranean mud dome fields. All major classes of archaeal lipids are present in the studied sediments, including isoprenoid glycerol diethers, isoprenoid glycerol dialkyl glycerol tetraethers, and irregular isoprenoid hydrocarbons. Of the compounds present, many, including a novel glycerol tetraether and sn-3-hydroxyarchaeol, have not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
179
0
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 266 publications
(197 citation statements)
references
References 54 publications
13
179
0
5
Order By: Relevance
“…Indeed, changes in CL distributions reflecting input of sedimentary methane-oxidizing Euryarchaeota have been observed in other sulfate-methane transition zones (e.g. Pancost et al, 2001;Weijers et al, 2011). These zones likely contain highly active archaeal communities which are productive over prolonged time periods, in an anoxic environment and thus slower degradation kinetics.…”
Section: Sedimentary Production and Preservation Of Gdgtsmentioning
confidence: 98%
See 1 more Smart Citation
“…Indeed, changes in CL distributions reflecting input of sedimentary methane-oxidizing Euryarchaeota have been observed in other sulfate-methane transition zones (e.g. Pancost et al, 2001;Weijers et al, 2011). These zones likely contain highly active archaeal communities which are productive over prolonged time periods, in an anoxic environment and thus slower degradation kinetics.…”
Section: Sedimentary Production and Preservation Of Gdgtsmentioning
confidence: 98%
“…GDGTs are preserved well in the sedimentary record and can thus be used as biomarkers for this group of Archaea (e.g. Kuypers et al, 2001;Pancost et al, 2001;Ingalls et al, 2006;Coolen et al, 2007). Schouten et al (2002) found a correlation between sea surface temperature (SST) and the distribution of four specific GDGTs present in sediment core tops (GDGT-1, -2, -3 and -4 0 , Fig.…”
Section: Introductionmentioning
confidence: 99%
“…However, the core lipids are very stable over geological time scales (Pease et al, 1998;Schouten et al, 2013) and can be found in many different habitats (Bischoff et al, 2013;Schouten et al, 2013). Past bacterial (branched GDGTs (Weijers et al, 2006)) and archaeal (isoprenoid-GDGTs (Koga et al, 1993;Pancost et al, 2001)) markers provide information on the abundance and most likely also on the activity of microbial communities in the geological past. Periods of increased OM accumulation 20 and increased past microbial activity can be observed in the Yedoma deposits (MIS 3 and 4).…”
Section: Signals Of Present and Past Microbial Communities In Permafrmentioning
confidence: 99%
“…Ar is one of the most common core ether lipids in archaea and is especially prominent in thermophiles, halophiles, and methanogens [46]. Ar is universally present in anaerobic sediments at cold seeps associated with gas hydrates, modern methane seep systems, and methane-rich mud volcanoes [8,[46][47][48]. In AOM environments, the incorporation of methane derived from carbon into these lipids is indicated by their very low δ 13 C values.…”
Section: Identification Of Aom Lipid Biomarkersmentioning
confidence: 99%
“…Because archaeal anaerobic methanotrophy results in highly 13 C-depleted lipids, monocyclic MDGD is derived from methanotrophic archaea [54]. This type of archaea biosynthesize structurally related GDGTs containing biphytane chains with one or two cyclopentane rings [48,56,57]. The thermophilic methanogen Methanococcus jannaschii is the only archaeon known to contain the macrocyclic diether as its core membrane lipid [58].…”
Section: Identification Of Aom Lipid Biomarkersmentioning
confidence: 99%